Some remarks on the monotone iterative technique - Buică, Adriana (Rev. Anal. Numér. Théor. Approx., 2002)
We consider an abstract operator equation in coincidence form \(Lu=N(u)\) and establish some comparison results and existence results via the monotone iterative technique. We use a generalized iteration method developed by Carl-Heikkila (1999). An application to a boundary value problem for a second-order functional differential equation is considered.